(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article presents the socio-historical traditions and modern approaches to reading and literacy development, as well as information about the literacy culture in Uzbekistan. In this sense, the article analyzes the purpose of the socio-historical traditions of reading books and the development of reading.